The Relationship between Religion and State: The Role of Islamic Politics in the Development of Democracy in Indonesia - Widia, Amanda Putri; Kurniawan, Heri; Bustomi, Yazid Imam; Hj Osmara, Nurninashahawana (Yayasan Abdurrauf Cendekia Nusantara, 2025)
Political Islam in Indonesia plays an important role in democratic development, although it is often faced with challenges in managing the relationship between religion and the state. As a Muslim-majority country, the application of Islamic values in politics raises debates about its compatibility with democratic principles such as freedom, equality and pluralism. On the one hand, Islamic politics can strengthen political ethics and social justice, but on the other hand, it has the potential to trigger polarization if not managed properly. This research explores the contribution of Islamic politics to democracy in Indonesia, particularly in instilling ethical values, strengthening public participation, and building inclusive dialogue. Using a qualitative approach and literature review, this research analyzes literature that discusses the role of Islamic politics in Indonesia's democratic dynamics. The results show that Islamic politics contributes through the values of justice, welfare, and transparency, as well as expanding political participation through religious parties and organizations such as NU and Muhammadiyah. Islamic politics also plays a role in creating interfaith dialogue and resolving social conflicts. The findings confirm the importance of inclusive and democracy-oriented Islamic politics to unite plural societies. However, this research is limited to a literature review, so a field study is needed for a more comprehensive understanding. Abstrak: Politik Islam di Indonesia memainkan peran penting dalam pembangunan demokrasi, meskipun sering dihadapkan pada tantangan dalam mengelola hubungan antara agama dan negara. Sebagai negara dengan mayoritas Muslim, penerapan nilai- nilai Islam dalam politik kerap memicu perdebatan mengenai kesesuaiannya dengan prinsip demokrasi seperti kebebasan, kesetaraan, dan pluralisme. Di satu sisi, politik Islam dapat memperkuat etika politik dan keadilan sosial, tetapi di sisi lain, ia berpotensi menimbulkan polarisasi sosial jika tidak dikelola dengan baik. Penelitian ini bertujuan mengeksplorasi kontribusi politik Islam terhadap demokrasi di Indonesia, khususnya dalam menanamkan nilai-nilai etis, memperkuat partisipasi publik, dan membangun dialog inklusif di tengah masyarakat yang beragam. Dengan pendekatan kualitatif dan kajian pustaka, penelitian ini menganalisis literatur akademik tentang peran politik Islam dalam dinamika demokrasi Indonesia. Hasilnya menunjukkan bahwa politik Islam berkontribusi melalui nilai-nilai keadilan, kesejahteraan, dan transparansi dalam pengelolaan negara. Partai-partai berbasis Islam serta organisasi seperti NU dan Muhammadiyah turut memperluas partisipasi politik bagi kelompok yang kurang terwakili. Selain itu, politik Islam juga berperan dalam menciptakan dialog lintas agama dan menyelesaikan konflik sosial. Temuan ini menegaskan pentingnya politik Islam yang inklusif dan berorientasi pada nilai-nilai demokrasi untuk mempersatukan masyarakat plural Indonesia. Namun, penelitian ini terbatas pada kajian pustaka tanpa analisis empiris, sehingga diperlukan penelitian lanjutan dengan metode studi lapangan untuk pemahaman yang lebih komprehensif. Kata kunci: Politik Islam, Demokrasi, relasi Agama dan Negara